2016
DOI: 10.1111/1745-9125.12122
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender, and the Crime of Crimes: Toward a Life‐course Theory of Genocide Participation*

Abstract: This article asks whether genocide follows the age and gender distributions common to other crime. We develop and test a life‐course model of genocide participation to address this question using a new dataset of 1,068,192 cases tried in Rwanda's gacaca courts. Three types of prosecutions are considered: 1) inciting, organizing, or supervising violence; 2) killings and other physical assaults; and 3) offenses against property. By relying on systematic graphic comparisons, we find that the peak age of those tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 80 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Universalizing responsibility for social issues such as climate change detracts from an acknowledgment of the systems and groups primarily responsible for these global harms that disproportionately impact women and other vulnerable populations (Wonders & Danner, 2015). With respect to mass atrocities such as genocide, Nyseth Brehm et al (2016) observed that the de-emphasis of social characteristics such as gender is common in the literature, which often focuses on men but does not analyze gender.…”
Section: Mainstream Violence Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Universalizing responsibility for social issues such as climate change detracts from an acknowledgment of the systems and groups primarily responsible for these global harms that disproportionately impact women and other vulnerable populations (Wonders & Danner, 2015). With respect to mass atrocities such as genocide, Nyseth Brehm et al (2016) observed that the de-emphasis of social characteristics such as gender is common in the literature, which often focuses on men but does not analyze gender.…”
Section: Mainstream Violence Researchmentioning
confidence: 99%
“…Gendered violence is more than a moment of aggression; it is the result of a “social template” developed in the years prior to the violence that set the stage for the violence to unfold (Hollander & Pascoe, 2019). Nyseth Brehm et al (2016) illustrated this idea in their research on the 1994 Rwandan genocide. The gendered norms, practices, and institutions of manhood and “good citizenship” existed well before the genocide unfolded (Nyseth Brehm et al, 2016).…”
Section: A Refined Theoretical Framework On Gender and Violencementioning
confidence: 99%
See 1 more Smart Citation
“…30 The literature within international criminology continues to grow in sophistication and nuance as more field-research is done and scholars increasingly seek to move beyond the sociopsychological experiments that dominated the field for such a long time. 31 Traditional theories are currently modified and refined to the specific circumstances of international crimes 32 , new theories are developed within criminology and related disciplines 33 and more traditional theories, including life course analysis 34 , are used to study the perpetrators of international crimes. The focus of the abovementioned literature, however, continues to lay predominantly with the lower ranking perpetrators.…”
Section: International Criminology: the Perpetratorsmentioning
confidence: 99%
“…This indicator is not significantly associated with the level of violence. Given recent findings that many perpetrators were in their mid‐30s (Nyseth Brehm, Uggen, and Gasanabo, ), model 4 assesses the percentage of middle‐aged men, which is also not significantly associated with the level of violence.…”
mentioning
confidence: 99%